Perencanaan Strategis Sistem Informasi Pada Institusi Pendidikan Tinggi Menggunakan Analisis Critical Success Factors - Widyaningsih, Pipin; Mustafid, Mustafid; Rochim, Adian Fatchur (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
There  are  many  organization  which  develop  their  information  technology  only  based  on  the  recommendation  of  certain  vendors  and colleagues. The development of Information and Technology Systems need a proper consideration in order to avoid the chance of bigger loss in the financial and investation sectors. The unsystematic development of Information and Technology Systems will not fu lfil a long term needs, there is no priority scale on it and it is not in line with the bu ssiness organization rhyme. The Strategic Planning Information System is a systematic approach about what is considered to be the most effective and effecient to fulfil the needs of information. The Strategic Planning Information System stated by Ward and Peppard (2002), which becomes the basis of this research, uses some analysis methods, likeValue Chain and Critical Success Factors. The result of this research is a blue print of the strategic planning which is based on  the  bussiness  organization  planning  with  the  data  gathered  through  the  analysis  method  used  and  it  involves  all  the  organization component.Keywords: Strategic planning information system; Higher education institution, Critical success factors